Algorithm and private autonomy (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The article presents a comment of a recent ruling of the Italian Court of Cassation on algorithms and data protection. The judgement addressed in an exemplary manner the issue of the protection of personal data processed through the use of an algorithm in order to generate reputational profiles of natural and legal persons to be used in private law employment relationships.
Keywords: Protection of personal data; algorithm; reputational profiles; private law